Wireless power transfer using the concept of magnetic coil resonant system - Muhammad Fitra; Elvy Elvy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Long life lithium ion batteries and methanol fuel cells have been persuaded as ways to make the electrical components more mobile, consumers expectations are still far from being met due to the added weight and expenses for battery replacement. The discovery of wireless power transfer as a new option, and holds great promise to leave the oversized battery. The design of wireless power transfer applies the concept of Magnetic Coil Resonant System (MCRS). The concept of MCRS is similar with a function of an antenna to transfer the power from one point to another. Multisim13.0 software is applied to predict the performance of the proposed MCRS. This software simulation is useful to estimate the output wave on the virtual oscilloscope and to obtain the reading of output voltage from the virtual multimeter. The transmitter side contains power supply, transmitter oscillator circuit and transmitter magnetic coil. Transmitter circuit convert DC to AC waveform and the receiver circuit convert AC to DC voltage. The DC Source that connected to Transmitter was provided by the DC source regulator acts as DC source to adjust Voltage and Current separately. The project show the efficiency of the wireless power transfer with different coil diameter and a distance between the transmitter and receiver coil. At a distance of 15 cm, power are successfully transmitted as it is indicated by the LED light to turn on. The increment of size in coil diameter has given a higher power and longer coverage distance for wireless transfer power.